Outpatient Cardiac Rehabilitation Suppresses Deterioration of Renal Function in Patients ≥75 Years of Age With Heart Disease - Sasamoto, Yuichiro; Endo, Noriko; Kanazawa, Kohko; Utsumi, Taeko; Takahashi, Tomomi; Endo, Yosuke; Nanba, Makoto; Takeda, Hiroto; Takano, Tomohiro; Takahashi, Koki; Tanji, Masahiro; Kohzuki, Masahiro (Circulation Journal, 2021)
Background:This study investigated the effect of outpatient cardiac rehabilitation (OCR) and physical activity on the estimated glomerular filtration rate based on serum cystatin C (eGFRcys) in patients with heart disease (HD) aged ≥75 years.Methods and Results:This non-randomized prospective intervention study involved 136 patients (non-OCR group, n=66; OCR group, n=70), 55 of whom were aged ≥75 years (non-OCR group, n=29; OCR group, n=26). Renal function (eGFRcys) was evaluated at discharge and 3 months thereafter. A linear mixed model (LMM) was used to assess changes in renal function over time. The hospital readmission rate within 3 months after discharge was also evaluated. LMM analysis showed that the change in eGFRcys was −2.27 and +0.48 mL/min/1.73 m2in the non-OCR and OCR groups, respectively (F=2.960, P=0.022). Further, among patients aged ≥75 years in the non-OCR and OCR groups, the change in eGFRcys was −3.83 and −1.08 mL/min/1.73 m2, respectively (F=2.719, P=0.039). The proportion of patients aged ≥75 years who were rehospitalized due to exacerbation of HD was 16.9% (n=10) and 6.7% (n=2) in the non-OCR and OCR groups, respectively.Conclusions:Among patients with HD aged ≥75 years, participation in OCR reduces the decline in renal function and hospital readmission rates.